Solution Precursor Plasma Spray System - Sanpo, Noppakun (SpringerBriefs in Materials, 2014)
This Brief describes the influence of the different organic chelating agents on the topography, physical properties and phases of SPPS-deposited spinel ferrite splats. The author describes how by using the SPPS process, the coating is produced directly from a solution precursor and how all physical and chemical reactions such as evaporation, decomposition, crystallization and coating formation occur in a single step. The author details not only the innovative approach to liquid feeding, but also focuses on its effects on the spinel ferrite system. The results of experimentation as well as detailed explanations of the experiments are included.